IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society 2014
DOI: 10.1109/iecon.2014.7049224
|View full text |Cite
|
Sign up to set email alerts
|

Online calculation of operational force in bilateral control system under time-delay

Abstract: This paper proposes a method to calculate operational force in time-delayed 4-channel bilateral control systems. In 4-channel bilateral control systems, operational force becomes unnecessary force for haptic sense transmission. Under timedelay, it is known that this force becomes larger than the force without time-delay. In this paper, it is shown that new force, communicative operational force, is generated in time-delayed 4-channel bilateral control, and a method for calculating the force is proposed. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Power factor calculated by dividing active power by apparent power. Then, power factor in mechanical system is defined as (13).…”
Section: Power Factor In Mechanical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Power factor calculated by dividing active power by apparent power. Then, power factor in mechanical system is defined as (13).…”
Section: Power Factor In Mechanical Systemmentioning
confidence: 99%
“…Ohno proposed an online calculation method of operational force under time delay [13]. From this research, it can be said the cause of operational force under time delay is position controller because the operational force corresponds to position controller.…”
Section: Introductionmentioning
confidence: 99%
“…2) Contact motion: In contact motion, 4ch scheme is based on Newton's second law; f = mẍ (10) and this is the reason of destabilization. In 4ch scheme, master transmits accelerationẍ to slave, and receives reaction force f caused by the acceleration.…”
Section: A Four-channel Schemementioning
confidence: 99%
“…Therefore, it has been considered that best scheme to keep contact stability is 4ch scheme with velocity feedback and how to design virtual damping is important [6]. In contrast, this paper proposes another approach to keep contact stability by rejecting delay element from (10). Proposed method is introduced in next section.…”
Section: A Four-channel Schemementioning
confidence: 99%
“…Although there are many researches about stability compensation [4]- [6], studies about operationality has been not performed enough. Therefore, the authors of this paper analyzed 4-channel bilateral control system under time delay and showed what operational force under time delay is [7]. The paper introduced a new concept, communicative operational force, and explained that operational force under time delay is the sum of operational force not under time delay and communicative operational force.…”
Section: Introductionmentioning
confidence: 97%